Penguatan Kesadaran Budaya Berbasis Kearifan Lokal Melalui Pembelajaran Sejarah - Andi Andi; Desvian Bandarsyah; Sulaeman Sulaeman (CHRONOLOGIA, 2023)
The approach of history education based on local wisdom has a positive influence on students' cultural awareness. Through this type of learning, students can understand the unique history, values, traditions, and culture of their community. This research utilizes a qualitative approach with a phenomenological method. Data is collected through interviews and documentation techniques. Interviews are conducted to directly obtain the research subjects' experiences, while documentation techniques are used to gather data from various sources. Data analysis follows a phenomenological analysis technique, involving three stages: narrating the phenomena experienced by the research subjects, classifying relevant statements, and analyzing these statements according to the subthemes of the study. History education based on local wisdom also encourages students to develop analytical skills. They are prompted to analyze historical contexts, consider different perspectives, and understand the impact of history on cultural development. This can enhance students' critical and analytical thinking abilities. In its implementation, history teachers play a crucial role in facilitating the strengthening of cultural awareness and local wisdom through history education. They select teaching materials that focus on local history and cultural wisdom. Teachers can also invite community figures, local history experts, or community members to share their knowledge and experiences with students. Overall, history education based on local wisdom has great potential to enhance students' cultural awareness, broaden their understanding of culture, and develop analytical skills as well as appreciation for the cultural heritage of society.